Analysis of a lift augmented hydrofoil for hydrokinetic turbines (2019)
In the last years, increased attention has been given to hydrokinetic energy technologies due to these turbines represent an attractive technology for the harnessing of a huge untapped renewable energy potential in oceans, seas but also in rivers and canals. However, the low efficiency is an important barrier to its commercialization. The aim of this study is to present the selection of a multi-element hydrofoil that can enhance the hydrokinetic turbine performance. Therefore, in order to examine the influence of the type of airfoil used, as multi-element hydrofoil, on the blade performance, several studies using JavaFoil software were performed. The result indicates that hydrofoil multi-element Eppler 420 can provide high efficiency of the turbine because it has a higher relationship between the lift and drag coefficients CLmax /CD (47.77) compared to the Selig S1223 profile (39.59) and other hydrofoils studied. Furthermore, computational fluid dynamics (CFD) was used to obtain the hydrodynamic characteristics of the hydrofoil Eppler 420 with and without flap. The CFD simulations were carried out using ANSYs-Fluent software. It was observed that there is an increase in the lift coefficient by 69.46% and 471.39 % for the hydrofoil with flap and a chord length of 30%, and a chord length of 70%, respectively, under the analyzed conditions with respect to the hydrofoil without flap. Keywords: multi-element blade, hydrokinetic turbine, hydrodynamic analysis, chord length, JavaFoil, 2D simulation